Synthesis of a benzotrisazulene via trioxobenzotrisazulene - Kirschbaum, Tobias; Rominger, Frank; Mastalerz, Michael (Universität, 2023)
A benzotrisazulene was synthesized on the basis of a truxene precursor by a series of Suzuki-Miyaura reactions via the intermediate trisoxo compound. The latter occurs in two forms (syn and anti), and the syn forms porous crystals.
Gesehen am 24.08.2023
Keywords: Forschungsdaten; Datenbank